Development of a Web-Based Agricultural Product Showcase System for Social Forestry Farmer Groups in Garut - Pamungkas, Bayu; Sidiq, Maulana; Septian, Luffi (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
This study aims to develop a web-based information system as a digital showcase for agricultural products by farmer groups under the Social Forestry Program in Garut Regency. The primary issue addressed is the limited market access and visibility of local agricultural products. The system was developed using the Agile methodology, enabling rapid iteration and user-driven adaptation. System design was modeled using Unified Modeling Language (UML), including use case, activity, class, and sequence diagrams. The platform was built with the CodeIgniter framework due to its efficiency and scalability in PHP-based applications. Key features include farmer group profiles, a product catalog, and an admin dashboard for data management. Data collection was conducted through field observation, semi-structured interviews, and document analysis. The results indicate that the system significantly enhances information accessibility, expands promotional reach, and strengthens the digital identity of farmer groups. These findings affirm that the application of information and communication technologies supports sustainable community-based digital agricultural transformation.